2010
DOI: 10.1257/mic.2.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Naïve Learning in Social Networks and the Wisdom of Crowds

Abstract: We study learning in a setting where agents receive independent noisy signals about the true value of a variable and then communicate in a network. They naïvely update beliefs by repeatedly taking weighted averages of neighbors' opinions. We show that all opinions in a large society converge to the truth if and only if the influence of the most influential agent vanishes as the society grows. We also identify obstructions to this, including prominent groups, and provide structural conditions on the network ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
750
5
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 846 publications
(772 citation statements)
references
References 30 publications
13
750
5
4
Order By: Relevance
“…There are many examples of loose social networks, such as friends, online networks, neighborhoods, ethnic groups, classrooms, clubs, and professional networks (e.g., close work colleagues). The size of loose social networks implies that the potential for strategic interaction is small (Golub and Jackson 2010).…”
Section: State Of the Artmentioning
confidence: 99%
“…There are many examples of loose social networks, such as friends, online networks, neighborhoods, ethnic groups, classrooms, clubs, and professional networks (e.g., close work colleagues). The size of loose social networks implies that the potential for strategic interaction is small (Golub and Jackson 2010).…”
Section: State Of the Artmentioning
confidence: 99%
“…described in work by French (1956) and Harary (1959), and was more completely specified and developed by DeGroot (1974). It has been used and extended by Besag (1974), Krause (2000), Friedkin and Johnsen (1997), DeMarzo, Vayanos, and Zwiebel (2003), Lorenz (2005), and Golub andJackson (2008, 2010), among many others. I will refer to it as the "DeGroot model."…”
Section: Learningmentioning
confidence: 99%
“…The divergence from Bayesian behavior comes from the fact that agents do not adjust their updating rule over time to account for the network structure: some friends may be talking to more people over time than others, and so forth. Despite this boundedly rational behavior, there are still many situations where the society eventually reaches a consensus that correctly approximates the unknown µ, as shown by Golub and Jackson (2010). Whether or not the DeGroot process converges to accurate estimate (and hence the Bayesian estimate) depends on how well balanced the relative weights are that different groups of agents place on each other.…”
Section: Learningmentioning
confidence: 99%
“…When social influence leads to correlated errors, both independence and diversity are reduced, which has been argued to compromise the reliability of the group judgment (9,(11)(12)(13)(14)(15)(16)(17)(18). In direct contrast with these results, however, theoretical models of social learning (19-21) have suggested that the effects of social influence on collective decisions vary based on the structure of the interaction network, predicting that, under the right conditions, social learning can lead a group's median judgment to improve (20)(21)(22)(23)(24).This prediction derives from the assumption that, when people learn about the beliefs of others, they revise their own beliefs to become more similar to their social referents (11, 12, 25, 26). Following the DeGroot model of social learning, this theory suggests that each individual's revisions are based on a weighted average of their own belief and the beliefs of their social referents (19).…”
mentioning
confidence: 99%